RIFM fragrance ingredient safety assessment, isoamyl salicylate, CAS registry number 87-20-7. (October 2015) - Api, A.M.; Belsito, D.; Bhatia, S.; Bruze, M.; Calow, P.; Dagli, M.L.; Dekant, W.; Fryer, A.D.; Kromidas, L.; La Cava, S.; Lalko, J.F.; Lapczynski, A.; et al.
Abstract: The use of this material under current use conditions is supported by the existing information. This material was evaluated for genotoxicity, repeated dose toxicity, developmental toxicity, reproductive toxicity, local respiratory toxicity, phototoxicity, skin sensitization potential, as well as, environmental safety. Repeated dose toxicity was determined using to have the most conservative systemic exposure derived NOAEL of 47 mg/kg/day. A dietary 13-week subchronic toxicity study conducted in rats on a suitable read across analog resulted in a MOE of 2350 while considering 10.3% absorption from skin contact and 100% from inhalation. A MOE of >100 is deemed acceptable. Highlights: Isoamyl salicylate safety assessment based on RIFM's criteria. Safety assessment based on 7 Human health endpoints plus environmental. Repeated dose toxicity was determined to have the most conservative NO[A]EL. An acceptable MOE was obtained.